The A to Z of the Philippines - Guillermo, Artemio R. (The A to Z guide series, 2010)
"The A to Z of the Philippines provides more than 400 hundred entries on important persons, places, events, and institutions, as well as salient economic, social and cultural aspects."--Publisher's description.